The prevalence and predictive factors of dentine hypersensitivity among adults in Turkey - Gunseli Katirci; Esra Uzer Celik (BMC, 2023)
Abstract Aim This study sought to determine the prevalence of dentine hypersensitivity (DH) among adults in Turkey. Also, to ascertain the association between DH and both etiological predictors and demographic patient characteristics. Material method Using a questionnaire and thermal and evaporative tests, 259 women and 209 men in the age range of 18 to 72 were analyzed. Individually, a clinical evaluation of DH signs was conducted. The DMFT index, gingival index, and gingival bleeding were reported for each subject. The gingival recession and tooth wear of sensitive teeth were also evaluated. Pearson Chi-square test was used to compare categorical data. Logistic Regression Analysis was used to examine the risk factors of DH. Data with dependent categorical variables were compared using the McNemar-Browker test. The significance level was p < 0.05. Results The average age of the population was 35.6 years. In the present study, a total of 12,048 teeth were analyzed. 1755 had thermal hypersensitivity (14.57%), while 470 experienced evaporative hypersensitivity (3.9%). The incisors were the teeth most impacted by DH, whereas the molars were the least affected. Exposure to cold air and sweet foods, gingival recession, and the presence of noncarious cervical lesions were all strongly linked to DH (Logistic regression analysis, p < 0.05). The cold stimulus increases sensitivity more than the evaporation stimulus. Conclusion Significant risk factors for both thermal and evaporative DH include cold air, consumption of sweet food, presence of noncarious cervical lesions, and gingival recession. More epidemiological research in this area is still required to fully characterize the risk factors and implement the most effective preventive interventions.